Emotional reactions towards COVID-19 among persons with diabetes. Issue 2 (11th May 2021) - Shinan-Altman, Shiri; Levkovich, Inbar
Abstract: The emotional impact of the coronavirus disease 2019 (COVID-19) pandemic on populations at large is emerging in the literature. However, the emotional response of persons with diabetes to the pandemic is only now beginning to emerge. Therefore this study aimed to identify factors contributing to emotional reactions towards this pandemic among persons with diabetes. A total of 205 persons with diabetes participated in this cross-sectional online survey between 14 May and 22 June 2020. Participants completed measures of emotional reactions towards COVID-19, perceived diabetes status, perceived susceptibility, knowledge about COVID-19, sense of mastery and sociodemographic questionnaires. Statistical analyses included Pearson correlations and regression analysis. According to the results, the mean score of negative emotional reactions towards COVID-19 was 3.45 (standard deviation 1.11, range 1–5), meaning that the score was relatively high. Higher levels of negative emotional reactions towards COVID-19 were associated with higher perceived susceptibility, greater knowledge about COVID-19 and a lower sense of mastery. The study's findings emphasize the need to communicate ongoing knowledge regarding COVID-19 and diabetes as well as to provide persons with diabetes with the necessary emotional support related to coping with diabetes and COVID-19.